L’évolution des pratiques rhétoriques de délibération publique par la controverse - Chantal Benoit-Barné; James McDonald (Communication)
This article aims to explain how the rhetoric of those involved in two public consultations about Hydro-Québec’s controversial project to construct a natural gas plant (the Suroît) in Beauharnois contributed to Quebec’s development of wind energy over the past years. In particular, the analysis reveals that the evolution of the rhetorical practices during these consultations fostered a new understanding of wind: whereas the wind was first an unpredictable force of nature that could be apprehended through direct experience and discussed in ordinary terms, it acquired a new discursive status as a natural resource that could be controlled and harvested.